2023
DOI: 10.3389/fpsyg.2023.1091605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of empathy training on the empathy level of healthcare providers in Ethiopia: a cluster randomized controlled trial

Abstract: ObjectiveEmpathy has deteriorated throughout clinical training and medical practice, and little is known about the effect of empathy training on the empathy level of healthcare providers. To address this gap, we assessed the effect of empathy training on the empathy level of healthcare providers in Ethiopia.DesignA cluster randomized controlled trial study design was conducted from 20 December 2021 to 20 March 2022. The empathy training intervention was conducted for three consecutive days.SettingThe study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…The finding that those who work 45 h a week have higher empathy levels than those who work overtime, suggests that self-care can be explained by a balanced life and good psychological health. There are also studies with similar findings (Hurissa et al, 2023;Klim et al, 2023).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The finding that those who work 45 h a week have higher empathy levels than those who work overtime, suggests that self-care can be explained by a balanced life and good psychological health. There are also studies with similar findings (Hurissa et al, 2023;Klim et al, 2023).…”
Section: Discussionsupporting
confidence: 54%
“…In the study, it is thought that married individuals, those with children and extended families and those with good family relations have higher levels of empathy due to factors such as having a greater sense of responsibility, supporting each other socially and establishing open communication between family members. There are also findings supporting this situation in studies in the literature (Hurissa et al, 2023;Jeffrey, 2016;Klim et al, 2023). The finding that those who work 45 h a week have higher empathy levels than those who work overtime, suggests that self-care can be explained by a balanced life and good psychological health.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, the results of this study were similar to those found in educational studies. In a cluster randomized controlled trial conducted by Hurissa et al (2023), empathy training for three consecutive days including video show, roleplaying, and storytelling about patient condition increased the total mean empathy scores of healthcare providers significantly (Hurissa, Koricha, & Dadi, 2023). Additionally, Kagawa et al (2023) reported that listening to patient storytelling could increase the mean scores of empathy among undergraduate medical students (Kagawa et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…randomized controlled trial conducted byHurissa et al (2023), empathy training for three consecutive days including video show, roleplaying, and storytelling about patient condition increased the total mean empathy scores of healthcare providers significantly36 . Additionally,Kagawa et al (2023) reported that listening to patient storytelling could increase the mean scores of empathy among undergraduate medical students37 .…”
mentioning
confidence: 98%